Analysis of Expatriate Cross-Cultural Leadership on Job Satisfaction and its Implications on Employee Performance - Ira Valentina Silalahi; Dikdik Purwadisastra (Almana : Jurnal Manajemen dan Bisnis, 2022)
The influence of globalization brings a phenomenon, namely the ASEAN Economic Community (MEA) or the ASEAN Economic Community (AEC). Globalization has a great influence on the world of industry and organizations, namely connecting industrial and organizational activities to be without boundaries. In the company that the author will examine, namely PT. Krakatau Daedong Machinery, located in Indonesia, Cilegon, Banten, has not been able to stabilize basic sales revenue. This phenomenon indicates the low performance of employees. The high and low performance of the employee is predicted by the level of the variables that influence it, namely expatriate cross-cultural leadership and job satisfaction. This study uses a survey with the type of verificative explanation research on 96 employees. Analysis and interpretation of the results of data processing using descriptive analysis and verification analysis (Partial Least Square). The results of the analysis show that the variable cross-cultural leadership of South Korean expatriates is included in the high category while the variables of job satisfaction and performance are included in the moderate category and the strengths and weaknesses of South Korean cross-cultural leadership have a positive and significant influence on the level of job satisfaction and employee performance. The level of job satisfaction has a positive and significant influence on the level of employee performance.